The Glacier Views of Jean-Antoine Linck – A Milestone for the Mont Blanc Glacier History from the 18th to the 19th Century - Samuel U. Nussbaumer; Heinz J. Zumbühl (Revue de Géographie Alpine)
Interdisciplinary approaches are needed to reconstruct the behaviour of glaciers beyond the beginning of systematic measurements. For example, historical documents have been used to reconstruct former glacier extents successfully at different sites, including in the well-documented Mont Blanc area that became popular since the mid-18th century among artists, scientists, and travellers. Jean-Antoine Linck from Geneva is probably the artist to whom we owe the greatest number of unique glacier views. Linck’s special preference were the ice regions, which he discovered and drew with alpinistic daring and naturalistic correctness, preferably by gouache, although many pencil sketches are preserved. Linck subtly used the etching technique to create easily reproducible plates in large format, which are then hand-coloured with gouache and watercolour. This technique allowed him to create numerous reproductions of the same view, while still giving them a unique and original aspect, views that are remarkable for their serenity and silence, while offering luminous atmospheres. These illustrations introduced the realistic representation of the high mountains into the iconography of Genevese painting and thus led to a new kind of landscape painting with a permanent character. From a perspective of glacier history and although many of his artworks are not exactly dated by the author, the work of Jean-Antoine Linck is indispensable since it represents the whole development, specifically of the Mer de Glace and the Glacier des Bossons, but also other glaciers during the period from the end of the 18th century until the 19th century glacier maximum around 1820. Linck’s work has the same importance for the Mont Blanc area as that of Caspar Wolf and Samuel Birmann for the central Swiss Alps or Thomas Ender for the Austrian Alps in terms of glacier iconography. Therefore, Linck was both an artist and a glacier historian.